Sistema integral de la jornada electoral - Pérez Islas, Amelia; Uribe Gutiérrez, José del Carmen; Muñoz de León, Mario Alberto (My University, 2013)
Sistema integral de la jornada electoral
Sistema integral de la jornada electoral
Keywords: Sistema integral de la jornada electoral